The relationship between tourism involvement, organizational commitment and organizational citizenship behaviors in the hotel industry - Chien Mu Yeh (Tourism and Hospitality Management, 2019)
Purpose – Due to the important role of hotel frontline employees in the service encounter, hotel firms strive to understand factors influencing frontline employees’ working attitudes and behaviors. The main purpose of the current study is to enrich this understanding by examining the interrelationships among tourism involvement, organizational commitment and organizational citizenship behaviors (OCBs). Design –Based on the recovery theory, tourism involvement was hypothesized to influence both organizational commitment and OCBs. Committed employees were hypothesized to be more likely to perform OCBs. The current study further hypothesized a mediating role of organizational commitment in the relationship between tourism involvement and the OCBs. Methodology –Measurements of tourism involvement, organizational commitment, and the OCBs were developed. A total of 336 frontline employees from 20 international hotels in Taiwan voluntarily participated in the current study. Their responses were examined by using independent t -tests, confirmatory factor analyses, and structural equation modelling. Findings –The outcomes demonstrate that tourism involvement positively influenced organizational commitment. Both tourism involvement and organizational commitment positively influenced the OCBs. The organizational commitment was found to be a mediator between tourism involvement and the OCBs. Originality of the research –The most extant studies examined factors influencing the development of organizational commitment and the OCBs by using work-related variables. However, they ignored contributions made by tourism to employees’ work life. The originality of the current study is the link of the non-work variable to work-related attitude and behavior. As such it provides a new insight to managing tourism human resources.